THE WORLD IN 2015: A SURVEY OF MAJOR TRENDS AND DRIVERS - Cabalu, Helen (The journal of contemporary issues in business and government, 2007)
Economic factors, environmental and social issues, and business and industry developments will all play a major role in the global landscape of the future. Increasing globalisation and market liberalisation and the onrush of new technology have already started to occur. The need to protect the environment, an active ageing of the population combined with a slowing population growth, and a significant structural change in consumption are among the many important challenges for national governments and industrial giants which have dominated almost every aspect of society. This paper reviews emerging trends and drivers which are of critical importance for the future.